Team Production, Sequential Investments and Stochastic Payoffs - Christoph Lülfesmann (University of Bonn, Bonn Graduate School of Economics (BGSE), 2000)
We investigate a team production problem where two parties sequentially invest to generate a joint surplus. In this framework, it is possible to implement the first best even if the investment return is highly uncertain. The optimal contract entails a basic dichotomy: it is a simple option contract if the investments of both parties are substitutive, and a linear incentive contract if they are complementary. These schemes can be interpreted in terms of asset ownership: for the case of substitutive investments, a conditional ownership structure is optimal while for complementary investments shared equity in combination with a bonus component renders efficiency feasible. In either case, the parties renegotiate the initial arrangement after the first party invested.
Keywords: D23; K12; L23; 330; Team Production; Asset Ownership; Sequential Investments